Analysis of PAF and NAF Tests Using NAPP and ANC Methods at Hajak Site, North Barito, Central Borneo - Sandan, Stephani; Nurcholis, Muhammad (Journal of Earth and Marine Technology (JEMT), 2024)
Acid mine drainage (AMD) is a significant challenge for the global coal mining industry, necessitating specialized treatment to prevent its occurrence. A crucial step in AMD prevention is identifying rocks that contribute to its formation. These rocks are classified into Potential Acid-Forming (PAF) rocks and Non-Acid-Forming (NAF) rocks. PAF rocks have the potential to produce acid, while NAF rocks do not. Laboratory analyses, including Maximum Potential Acidity (MPA), Acid Neutralizing Capacity (ANC), Net Acid Producing Potential (NAPP), and Net Acid Generating (NAG) tests, identified 3 sample points with potential PAF characteristics out of 35 samples tested (see Table 3.1). Among these, 2 sample points were classified as Potential Acid Forming-Low Capacity, and 1 sample point was categorized as Potential Acid Forming-Medium Capacity (NAG pH 4.5, NAPP 10 kg H2SO4/ton). The acidity level of mine water resulting from landfilling varies significantly based on the mineral content and landfilling techniques used. Mined material with high carbonate mineral content tends to have lower acidity levels in leachate and can even neutralize formed acid. The stockpiling strategy implemented involves layering PAF material followed by a final cover of NAF material and a rooting zone to mitigate acid formation.